SUMBANGAN PEMIKIRAN HAK ASASI MANUSIA TERHADAP PEMBAHARUAN KITAB UNDANG-UNDANG HUKUM ACARA PIDANA(KUHAP) - Ari Wibowo (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2016)
The idea of renewal of the Criminal Procedure Code can not be separated from the contribution of human rights concept. This contribution has been explicitly included in the preamble of the Draft of Criminal Procedure Code. Although the current Criminal Procedure Code already provides protection to the rights of the defendant, but the implementation is still not optimal. Therefore, in the Draft of Criminal Procedure Code there is a new institution called the Rechter-Commissaris to replace the function of Pretrial Institutions. It has far wider powers of Pretrial Institution, so that the protection of the rights of defendant in any stage of the judicial process will be more secure fulfillment. The development of human rights concept also contributed to the idea to regulate the rights of victims, both associated with involvement in all stages of judicial proceedings and the right to sue for damages.